2019
DOI: 10.3390/ani9121073
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of a Detailed Mineral Profile of Meat with Animal Performance and Beef Quality

Abstract: The mineral profile of beef is a subject of human health interest, but also animal performance and meat quality. This study analyzes the relationships of 20 minerals in beef inductively coupled plasma-optical emission spectrometry (ICP-OES) with three animal performance and 13 beef quality traits analyzed on 182 samples of Longissimus thoracis. Animals’ breed and sex showed limited effects. The major sources of variation (farm/date of slaughter, individual animal within group and side/sample within animal) dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In the survey of Piemontese young bulls, the variability for SEUROP score was similar to that found in this study, whereas variability was higher than in this study for carcass weight and, especially, age at slaughter (Savoia et al, 2019b). Slightly higher than in this study was also the farm effect found in a survey on Chianina and Romagnola young bulls and heifers slaughtered according to the protected designation of origin of "Vitellone bianco dell'Appennino Centrale" by the European Union (Patel et al, 2019).…”
Section: Performance Of Crossbred Calves For Veal and Beef Productionsupporting
confidence: 84%
“…In the survey of Piemontese young bulls, the variability for SEUROP score was similar to that found in this study, whereas variability was higher than in this study for carcass weight and, especially, age at slaughter (Savoia et al, 2019b). Slightly higher than in this study was also the farm effect found in a survey on Chianina and Romagnola young bulls and heifers slaughtered according to the protected designation of origin of "Vitellone bianco dell'Appennino Centrale" by the European Union (Patel et al, 2019).…”
Section: Performance Of Crossbred Calves For Veal and Beef Productionsupporting
confidence: 84%
“…The selenium content in buffalo meat is comparable to that reported for beef [101] and could be increased by dietary strategies [109,110] to produce Se-enriched functional meat. Studies on mineral content in buffalo meat, apart from its importance in human nutrition, would be important to clarify its role in animal performance and beef quality traits, as demonstrated in bovine breeds [109,111]. Meat is rich in vitamins, which are essential nutrients involved in biological functions.…”
Section: Chemical Composition and Nutritional Propertiesmentioning
confidence: 99%
“…These researchers employed the principal components analysis (PCA) and hierarchical cluster analysis (HCA), an appropriate example of the applicability of this type of statistical approach. Similarly, Patel et al [33] used multivariate analyses to explore the relationship among animal and carcass characteristics, beef (longissimus thoracis) quality traits, and lean meat mineral composition (20 elements). In this case, the researchers employed a combination of univariate (simple correlation) and multivariate (factorial analysis) techniques that allowed them to compare the relationship between minerals, not only individually but also in a factorial fashion (five factors) with the animal/carcass performance and the beef quality traits.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the researchers employed a combination of univariate (simple correlation) and multivariate (factorial analysis) techniques that allowed them to compare the relationship between minerals, not only individually but also in a factorial fashion (five factors) with the animal/carcass performance and the beef quality traits. This study [33] only included the carcass weight as one of the three performance characteristics. Both previous investigations [32,33] indicate the need for studying complex relationships employing a multivariate approach, that may include a large number of variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation